A K (plus one) ARDS Modular Model to Improve Non-English Department English Teachers’ Competences in a Higher Education - Fransisca Endang Lestariningsih (Intelektual Pustaka Media Utama, 2018)
There are two types of English teachers in a higher education, English teachers who have English Language Teaching(ELT) background and those who do not have it. It brings about some problems in the teaching instruction and the achievement of the students, as well. This is a theoretical views used as a preliminary study to develop the model to improve English teachers’ competences in a higher education. A modular model proposed by Kumaravadivelu, with his KARDS model seems appropriate to be applied for the English teachers who are assigned to teach higher education students. This model is at first intended for the prospective teachers of L2 (TESOL), but with some modifications, it can be used to improve the competences of in-service English teachers.